Evaluation of nanolipoprotein particles (NLPs) as an in vivo delivery platform. - Nicholas O Fischer; Dina R Weilhammer; Alexis Dunkle; Cynthia Thomas; Mona Hwang; Michele Corzett; Cheri Lychak; Wasima Mayer; Salustra Urbin; Nicole Collette; Jiun Chiun Chang; Gabriela G Loots; et al. (PLoS ONE)
Nanoparticles hold great promise for the delivery of therapeutics, yet limitations remain with regards to the use of these nanosystems for efficient long-lasting targeted delivery of therapeutics, including imparting functionality to the platform, in vivo stability, drug entrapment efficiency and toxicity. To begin to address these limitations, we evaluated the functionality, stability, cytotoxicity, toxicity, immunogenicity and in vivo biodistribution of nanolipoprotein particles (NLPs), which are mimetics of naturally occurring high-density lipoproteins (HDLs). We found that a wide range of molecules could be reliably conjugated to the NLP, including proteins, single-stranded DNA, and small molecules. The NLP was also found to be relatively stable in complex biological fluids and displayed no cytotoxicity in vitro at doses as high as 320 µg/ml. In addition, we observed that in vivo administration of the NLP daily for 14 consecutive days did not induce significant weight loss or result in lesions on excised organs. Furthermore, the NLPs did not display overt immunogenicity with respect to antibody generation. Finally, the biodistribution of the NLP in vivo was found to be highly dependent on the route of administration, where intranasal administration resulted in prolonged retention in the lung tissue. Although only a select number of NLP compositions were evaluated, the findings of this study suggest that the NLP platform holds promise for use as both a targeted and non-targeted in vivo delivery vehicle for a range of therapeutics.